Improvements in Functional Status Among Survivors of Orthotopic Heart Transplantation Following High-risk Bridging Modalities. Issue 9 (September 2021) - Huckaby, Lauren V.; Hickey, Gavin; Sultan, Ibrahim; Kilic, Arman
Abstract : Background: The 2018 heart allocation change has resulted in greater frequency of high-risk bridging to orthotopic heart transplantation (OHT). Although survival has been studied in these patients, functional status outcomes are less established. This study evaluated changes in functional status of OHT survivors based on bridging strategy. Methods: Adults (≥18 y) undergoing OHT between January 2015 and March 2020 were stratified by bridging modality: no bridging, inotropes only, intra-aortic balloon pump (IABP), temporary ventricular assist device (VAD), durable VAD, and extracorporeal membrane oxygenation (ECMO). Using paired analysis, the Karnofsky performance scale (0–100) was utilized to compare differences in function at listing, transplant, and follow-up. Results: In total, 13 142 patients underwent OHT. At the time of both listing and transplant, patients requiring IABP, temporary VAD, and ECMO displayed the lowest functional status (each median 20) compared with other groups ( P < 0.001). Among survivors, the median performance status at follow-up was ≥80 for all groups, indicating total functional independence with no assistance required. Substantial improvement in Karnofsky score occurred from transplant to follow-up in survivors bridged with IABP (40), temporary VADs (60), and ECMO (50) (each P < 0.001). Among survivors with at least 90-day follow-up, the median Karnofsky score was 90 regardless of bridging modality. Conclusions: Despite a higher mortality risk, critically ill patients who survive OHT after bridging with high-risk modalities experience acceptable functional status outcomes. These findings are important to place in the context of the impact that the 2018 allocation change has had on the landscape of OHT in the United States. Abstract : Supplemental Digital Content is available in the text.